Ensuring the strength and ductility synergy in an austenitic stainless steel: single- or multi-phase hetero-structures design. (1st March 2021) - Li, Yong; Li, Wei; Li, Shilei; Min, Na; Jiang, Laizhu; Zhou, Qinglong; Jin, Xuejun
Abstract: Heterogeneous microstructures have been proposed to optimize the mechanical properties in the respect of strength and ductility synergy in many alloy systems. In this work, the multi-phase hetero-structured microstructure consisting of fine grains and coarse grains where the ferrite is embedded in the vicinity of the nano-grains was obtained by regulating the thermomechanical processing parameters. A yield strength of 1.2 GPa which is more than two times higher than the coarse grained counterpart with less uniform elongation loss is achieved in the multi-phase hetero-structured steel. The microscopic load transfer in this complex microstructure is investigated by the in situ high energy synchrotron X-ray diffraction. The persistent strain hardening is ascribed to the hetero-deformation induced stress associated with the joint activation of transformation-induced plasticity (TRIP) and twinning-induced plasticity (TWIP) effects. As a comparison, the single-phase hetero-structured steel exhibits little lower strength but higher uniform ductility. Graphic Abstract: Image, graphical abstract